DEVELOPMENT OF MANDIRI LEARNING MODEL BASED ON OPEN LEARNING IN LEARNING CALIBULUS IN PRODUCING MATHEMATICS EDUCATION UNIVERSITY STATE MAKASSAR - Arianti Arianti (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2017)
This research is categorized as research and development, refers to Plomp model (1997). This model consists of 5 steps, namely (a) first study step, (b) planning step, (c) realizing/construction step, (d) test, evaluation and revision step, and (e) implementation step. The results of the study reveal that (1) based on expert validation result, it is obtained that the instruments used in independent learning model based on opened questions (PMBST) is extremely valid, (2) the practical result of independent learning model based on opened questions through observation sheets instruments is in entirely conducted category, and the lecturer’s ability to manage the class is in average score of 3.5 (high qualification), (3) the effectiveness of independent learning model based on opened questions for 3 effectiveness components had been achieved, that: (a) the students’ activities had met the set ideal time (>75%), (b) the students’ response of independent learning model based on opened questions is in positive category, that 80% of the students give positive response on learning process, (c) the students’ learning achievements cover: (1) the students’ creativity in calculus problem solving obtained 63% for creative thinking criteria is in medium category, (2) the students’ learning independent in understanding calculus material is in positive category, there are 28 out of 39 students’ (72%) give positive response on independent learning, and (3) calculus material mastery in terms of completeness learning result, there are 34 out of 39 students’ (87%) obtained the score above 61